Medium to Large Terrestrial Mammals - Mohd Azlan, Jayasilan; Lok, Lisa Choy Hong; Sally, Soo Kaicheen (UNIMAS Publisher and Wilmar Plantations Sdn Bhd, 2023)
Mammals are one of the most susceptible taxa to local extinction because of habitat fragmentation and loss (Dirzo et al., 2014). Partly due to their sensitivity to their surrounding, mammals are often used for biodiversity assessments and monitoring programmes around the globe as they are reliable ecosystem quality indicators (Ahumuda et al., 2011). However, as tropical medium to large mammals are often cryptic and elusive in nature (Mohd-Azlan, 2006), they are difficult to study. Therefore comprehension of the persistence of medium to large mammals within forest fragments especially in agricultural landscapes in this region is important as they remain scarce in scientific literature. Remnant forest fragments within the plantation area may potentially provide refugia and support the existence of medium to large mammals as many studies have indicated that oil palm plantation harbours lower diversity of wildlife compared to forested areas.